Effect of agronomic management practices on soil fertility under jute (Corclzorus capsu1aris)-groundnut (Arachis hypogaea)-blac kgram (Plzaseolus mungo) cropping system - M. MISHRN; K. K. (Indian Journal of Agronomy, 2001)
A 2-year experinlent conducted on jutc (Corchous caps tlaris L.)-groundnut (Arachis hypogaeu I.,.)- blackgram (Phnsroltis n7ungo Id.) with varying management practices revealed that jute depleted organic carbon, total nitrogen, available phosphorus and potash contents of soil, whereas legumes like groundnut and blackgram improved the sanie in rotation. .4pplication of fertilizers in varied doses to crops increased the organic carbon, total nitrogen, availahlo phosphorus and potash contents of soil aftcr 2 years ofrotation. 1:artncrs practice and weed-free method of\.-ed control helped in building up of organic carbon, total nitrogen and available potash status but lowered the available phosphoms content coinpared with chemical, chemical + mechanical and unweeded control. Wider row spacings in crops helped in accci nulating higher organic carbon and total nitrogen but lowered the available phosphorus and potash contents compared with closer row spacing aAer 2-year rotation of jute–ground- nut-blackgram.